Estimation of the liquidity trap using a panel threshold model. Issue 16 (1st November 2016) - Peng, Fangping; Cebula, R. J.; Foley, M.; Zhan, Kai
ABSTRACT: This empirical study investigates, unlike previous studies, the presence of a liquidity trap using firm-level data. The study focuses on the case of China. A panel threshold model is employed. The empirical estimation reveals that the interest elasticity of money demand declines as the interest rate falls, a finding indicating that China has not been in a liquidity trap.